(untitled) (Asian Journal of Medical and Biological Research, 2026)
Childhood obesity has emerged as a major public health challenge worldwide, particularly in low- and middle-income countries that face the double burden of overnutrition and undernutrition. Bangladesh is currently experiencing a rapid nutrition and lifestyle transition. As a result, increasing rate of overweight and obesity among children and young people are contributing to elevated risk of non-communicable diseases and long-term health complications. This study aimed to synthesize recent evidence on the prevalence, determinants, and public health implications of childhood obesity in Bangladesh. A narrative review approach was utilized to examine national surveys, peer-reviewed articles, and global databases published in the last two decades. Findings show a rapid rise in childhood obesity. The prevalence of overweight among Bangladeshi children under 5 increased from 0.9% in 2000 to 2.4% in 2019, while overweight among adolescents aged 5-19 rose from approximately 3% in 2000 to over 9% in 2016. Similar upward trends are observed in obesity rates for both boys and girls. Multiple factors including rapid urbanization, shifting dietary patterns towards energy dense foods, increasing purchasing power, physical inactivity, academic pressure, lack of awareness among parents, and inadequate policy implementation contribute to this growing problem. Evidence based prevention strategies include accessible female friendly physical activity opportunities, structured urban planning with sufficient recreational activities, raising maternal awareness about obesity risks, and including nutrition education in school curriculum. Since, socioeconomic similarities of Bangladesh with its neighboring countries are common, insights from this review might also be applied to regional policy improvement. Therefore, addressing childhood obesity in Bangladesh requires effective strategies by involving policy makers, educators, and public health practitioners to mitigate the future burden. Asian J. Med. Biol. Res. 2026, 12(1), 5-15